Incidence of amyotrophic lateral sclerosis in southern Italy: a population based study. Issue 8 (15th July 2005) - Logroscino, G; Beghi, E; Zoccolella, S; Palagano, R; Fraddosio, A; Simone, I L; Lamberti, P; Lepore, V; Serlenga, L
Abstract : Background: While the incidence of amyotrophic lateral sclerosis (ALS) is similar across the world (range, 1.0 to 2.5/100 000), a latitude gradient from north to south has been observed. Objective: To determine the incidence of ALS in Puglia, a region of south eastern Italy, and to test the latitude gradient hypothesis comparing the present study with findings in studies conducted with the same design in a northern latitude. Methods: Puglia (4 086 613 residents in 2001) is the site of a multicentre-multisource prospective population based registry established in 1997. All incident ALS cases during the period 1998–99 were enrolled and followed up. Cases were classified using the first and the revised El Escorial criteria. Results: During the study period 130 cases were enrolled. The annual crude incidence for ALS in Puglia for the two year period 1998–99 was 1.6/100 000 (95% confidence interval, 1.3 to 1.9). The incidence was higher for men (incidence rate (IR) = 2.1 (1.7 to 2.7) than for women (IR = 1.2 (0.9 to 1.5)) in all age groups, with a male to female ratio of 1.6. For both men and women, the incidence increased through age 75 and declined rapidly afterwards. The mean annual incidence adjusted by age and sex to the 2001 Italian population was 1.7/100 000 (1.4 to 2.0). Conclusions: ALS incidence is within a narrow range across countries, with a peak between 65 and 75 years and a higher incidence in men. A north to south latitude gradient of ALS incidence is not supported by the results of cohort studies.